2020
DOI: 10.14744/nci.2020.23334
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Fat Thickness is Associated with Retinopathy in Patients with Newly Diagnosed Hypertension

Abstract: OBJECTIVE: Hypertensive retinopathy develops based on endothelial dysfunction, inflammation, and atherosclerosis. Epicardial fat secretes various cytokines associated with endothelial dysfunction, oxidative stress, inflammation, and atherosclerosis. We aimed to evaluate whether epicardial adipose tissue (EAT) thickness is a marker for retinopathy in newly diagnosed hypertensive patients. METHODS: A total of 73 newly diagnosed hypertension (HT) patients were included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…[8] Moreover, previous studies have shown the relationship between epicardial fat thickness (EFT) and the development of retinopathy in diabetic patients and newly diagnosed HT patients. [9,10] The EFT can be measured with different imaging techniques; these are echocardiography, magnetic resonance imaging (MRI), and multidetector computed tomography (CT), however echocardiography is a simple and noninvasive procedure, and echocardiographic measurements of EFT was shown to correlate well with MRI. [6] There is no study showing whether there is a relationship between EFT and the RVO.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Moreover, previous studies have shown the relationship between epicardial fat thickness (EFT) and the development of retinopathy in diabetic patients and newly diagnosed HT patients. [9,10] The EFT can be measured with different imaging techniques; these are echocardiography, magnetic resonance imaging (MRI), and multidetector computed tomography (CT), however echocardiography is a simple and noninvasive procedure, and echocardiographic measurements of EFT was shown to correlate well with MRI. [6] There is no study showing whether there is a relationship between EFT and the RVO.…”
Section: Introductionmentioning
confidence: 99%